Solar reactor for enhancing absorption based on light transmission control and spectrum regulation - WANG WENTING; ZHANG HAO; YANG DAZHI; KONG YU; ZHANG XIAOMI (2023)
The invention discloses a solar reactor for enhancing absorption based on light transmission control and spectrum regulation, and belongs to the field of solar thermochemistry. The existing solar reactor is limited in thermal efficiency, so that the reaction efficiency is poor. Sunlight converged by the disc-type solar condenser irradiates the interior of the spherical shell through the broadband optical quartz window sheet, one part of the sunlight is received by the graphite heat collection tube coated with the selective absorption coating, and the other part of the sunlight is reflected by the total reflection coating material on the inner surface of the spherical shell for multiple times. And finally, the sunlight is also received by the graphite heat collecting tube coated with the selective absorbing coating, the graphite heat collecting tube absorbs the energy of the sunlight to heat an internal catalytic material, at the moment, feed gas is introduced into the graphite heat collecting tube, the feed g